Electrochemical Reduction of CO2 in a Zero‐Gap Electrolyzer Cell on a Metal Molecular Electrocatalyst - Simphiwe L. Ndlangamandla; Shankara G. Radhakrishnan (ChemistryOpen)
Electrochemical reduction of CO2 (ECR) on transition metal‐containing porphyrin systems often leads to carbon monoxide. Herein, a modified zero‐gap polymer electrolyte membrane water electrolyzer is used with 5,10,15,20–tetraphenyl–21H,23H–porphine copper (II) as a cathodic electrocatalyst for ECR in 0.1 M NaOH as an aqueous catholyte. The setup yields CO, CH4, and C2H4 along with hydrogen evolution, with selectivity toward C2H4 formation as indicated by gas chromatographic analysis. Although hydrogen formation is predominant, the system yields a high average current density of 146.94 mA cm−2 and a Tafel slope of ≈226 mV dec−1 in concurrence. The cyclic voltammetric experiments show the stepwise formation of Cu (II) → Cu (I) → Cu (0) based on the potentials referenced against the reversible hydrogen electrode, which could have been the driving factor for the ECR.